PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN KOMPETENSI PEGAWAI TERHADAP KINERJA YANG DIMEDIASI OLEH KOMITMEN ORGANISASI PADA PEGAWAI KPU PROVINSI SULAWESI TENGGARA - Asmah Yanti Latif; Patwayati Patwayati; Aidin Hudani Awasinombu; Yusuf Montundu; Farhan Ramdhani Istianandar (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The research objective is to find out; 1) To examine and analyze the effect of work discipline on the organizational commitment of the KPU Secretariat employees of Southeast Sulawesi Province. 2) To examine and analyze the influence of the work environment on the organizational commitment of the KPU Secretariat employees of Southeast Sulawesi Province. 3) To examine and analyze the effect of employee competence on the organizational commitment of the KPU Secretariat employees of Southeast Sulawesi Province. 4) To examine and analyze the effect of organizational commitment on the performance of the KPU Secretariat employees of Southeast Sulawesi Province. 5) To examine and analyze the effect of work discipline on the performance of the KPU Secretariat employees of Southeast Sulawesi Province. 6) To test and analyze the influence of the work environment on the performance of the employees of the KPU Secretariat of Southeast Sulawesi Province. 7) To test and analyze the effect of employee competence on the performance of the KPU Secretariat employees of Southeast Sulawesi Province. 8) To examine and analyze the role of organizational commitment in mediating the effect of work discipline on the performance of the KPU Secretariat employees of Southeast Sulawesi Province. 9) To examine and analyze the role of organizational commitment in mediating the influence of the work environment on the performance of the KPU Secretariat employees of Southeast Sulawesi Province. 10) To examine and analyze the role of organizational commitment in mediating the effect of employee competence on the performance of the KPU Secretariat employees of Southeast Sulawesi Province. This research design is included in the survey research category because the main data collection uses an instrument in the form of a questionnaire. Survey research is research that takes a sample from a population and uses a questionnaire as a data collection tool. The population in this study were all Civil Servants (PNS) at the Secretariat of  the General Election Commission of Southeast Sulawesi Province and the Secretariat of the KPU in 17 regencies and cities totaling 279 people, so the determination of the number of samples for this study was determined using the Slovin formula (Sekaran, 2003). ). The type of data used in this research is quantitative. The data used are primary and secondary data. The data analysis method of this research is SEM (Structural Equation Model) analysis. The results showed that; 1) High work discipline has an impact on work discipline. 2) A high work environment will have an impact on organizational commitment. 3) High employee competence will have an impact on organizational commitment. 4) Good work discipline will have an impact on improving employee performance. 5) A good work environment cannot have an increasing impact on employee performance. 6) Good employee competence will have an impact on improving employee performance. 7) High organizational commitment has an impact on improving employee performance. 8) Work discipline has an impact on employee performance through organizational commitment. 9) the work environment has an impact on employee performance through organizational commitment. 10) Employee competence has an impact on employee performance through organizational commitment.